Clinicopathological Features of Primary Neuroendocrine Tumors of Gastrointestinal/Pancreatobiliary Tract With Emphasis on High-Grade (Grade 3) Well-Differentiated Neuroendocrine Tumors - Hashmi, Atif A (Cureus, 2021)
Introduction The two broad subcategories of neuroendocrine neoplasms (NENs) are well-differentiated neuroendocrine tumors (WDNETs) and poorly differentiated neuroendocrine carcinomas (PDNECs), based on tumor architecture and cytology. Grade 3 WDNETs are a subset of WDNETs that not only are high grade by mitotic activity or proliferative index but exhibit a well-differentiated histology. In this study, we evaluated the clinicopathological features of primary neuroendocrine tumors of the gastrointestinal (GI)/pancreatobiliary tract with emphasis on high-grade WDNETs, as it is a newly defined entity. Methods We conducted a retrospective observational study, including a total number of 122 cases of primary GI and pancreatobiliary tract NENs. Slides and blocks of all cases were retrieved from the departmental archives. Immunohistochemical stains including Ki67 were applied to selected tissue blocks of all cases. Tumors were then evaluated for their histological differentiation and tumor grade. Results Our results showed that the mean age of patients was 46.8 ± 17.1 years. Majority of the NENs were GI tract origin (86.9%). The most common site of tumor in gastroenteropancreatic tract was the small bowel (31.1%), followed by the stomach (26.2%). Ninety five percent of the tumors were WDNETs, of which the most common grade was G2. The mean Ki67 index was 15.8 ± 23.8. Grade 3 WDNETs were noted to have an older mean age than grades 1 and 2 WDNETs. Ten out of 102 (9.8%) WDNETs of GI tract were grade 3, compared with four out of 14 (28.6%) of pancreatobiliary tract.  Conclusion In this study, we found that high-grade (grade 3) WDNETs were more frequent in pancreatobiliary tract than GI tract. Moreover, high-grade WDNETs were associated with a higher mean age than low-grade (grade 1-2) WDNETs. It is extremely important to recognize this subset (high grade) of WDNETs and to distinguish it from PDNECs, as the latter are known to be associated with a worse overall survival. Despite high mitotic rate/proliferative index, high-grade WDNETs are characterized by organoid architecture and monomorphic cell population.